2015
DOI: 10.1002/fsn3.308
|View full text |Cite
|
Sign up to set email alerts
|

A study on sensory properties of sodium reduction and replacement in Asian food using difference‐from – control test

Abstract: This study examined the effects of sodium reduction and flavor enhancers on the sensory profile of two types of hawker foods commonly consumed in Singapore, namely chicken rice and mee soto broth. The ‘difference‐from‐control’ test was the method adopted in this study involving 24–29 trained panelists. Combinations included blind control, two levels of sodium reduction, and two levels of flavor enhancers in sodium‐reduced recipes. In the sodium‐reduced recipes, two levels of NaCl, 0.48% and 0.55%, for chicken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
1
21
0
3
Order By: Relevance
“…There is a synergistic effect between salty and umami taste. According to Leong, Kasamatsu, Ong, Hoi, and Loong (), MSG could reduce up to 40% of sodium from chicken broth without sacrificing palatability. Because of the comparatively larger molecular weight, addition of sodium from MSG is about one third of that from sodium chloride.…”
Section: Resultsmentioning
confidence: 99%
“…There is a synergistic effect between salty and umami taste. According to Leong, Kasamatsu, Ong, Hoi, and Loong (), MSG could reduce up to 40% of sodium from chicken broth without sacrificing palatability. Because of the comparatively larger molecular weight, addition of sodium from MSG is about one third of that from sodium chloride.…”
Section: Resultsmentioning
confidence: 99%
“…It is not clear in the case of MSG how umami influences liking. The increase in palatability by MSG is so robust that it can maintain the acceptability of food with reduced salt, which also works by improving the perception and flavor intensity in food [ 14 , 15 , 16 , 17 , 18 ]. That is, studies have confirmed that the partial substitution of salt by MSG allows for an overall decrease in sodium without reducing food palatability.…”
Section: The Traditional Japanese Diet and Its Potential Health Bementioning
confidence: 99%
“…Glutamate is the most abundant amino acid present in many protein‐containing foods such as meat, sea food, and aged cheese (Mouritsen and Styrbaek ; Hajeb and Jinap ; Kurihara ; Leong et al. ). Umami is expressed as increase in flavor characteristic, continuity, mouthfulness, impact, mildness, and thickness that gives enriching distinctive taste (Yamaguchi and Ninomiya ; Leong et al.…”
Section: Introductionmentioning
confidence: 99%
“…Umami is expressed as increase in flavor characteristic, continuity, mouthfulness, impact, mildness, and thickness that gives enriching distinctive taste (Yamaguchi and Ninomiya ; Leong et al. ). Therefore, the general objective of this study was to comparatively evaluate the flesh of C. gariepinus , H. bidorsalis , and their hybrids for nutritional and sensory attributes and specifically with regard to: (1) the proximate values of these species and their hybrids; (2) cognitive tastes: sweet, salty, sour, bitter, and umami ; and other qualitative parameters: texture, aroma, flavor, color, and overall acceptability.…”
Section: Introductionmentioning
confidence: 99%